Diderma aglomerospora (Didymiaceae, Physarales, Myxomycetes), a new species from Brazil - Barbosa, David Ítallo; Melo, Tiago Espósito O.; Brayner, Fábio André; Cavalcanti, Laise De Holanda (Phytotaxa, 2021)
Diderma aglomerospora is here proposed as a new species based on morphological analyses. The new species resembles D. badhamioides by possessing clustered spores but differs from it by the absence  of a columella and narrower filaments of the capillitium. The type material was developed in moist chamber assembled with bark of live trees from a restinga forest environment in the Guadalupe Environmental Protection Area, Pernambuco, Northeast Brazil. Sporocarps are described and illustrated, and comments on characteristics of the microhabitat are provided.